AGRICULTURAL TECHNOLOGY OF CULTIVATION OF AMARANTH MEDICINAL PLANT (AMARANTHUS) AND ITS MEDICINAL PROPERTIES (Scientific journal of the Fergana State University, 2025)
In medicine, the oil obtained from the amaranth (Amaranthus) plant helps to heal stomach and intestinal ulcers, skin diseases, cut wounds faster and in the treatment of light diseases, especially amaranth seeds prevent the growth of malignant tumors caused by cancer, it is widely used as a medicine when taken and absorbed. Medicinal amaranth belongs to such medicinal plants. And this article, what is about profitable spices, we discuss about the medicinal properties of the plant and its cultivation.